Case Report: Overlapping Multiple Sclerosis With Anti-N-Methyl-D-Aspartate Receptor Encephalitis: A Case Report and Review of Literature - Huang, Ying; Wang, Qian; Zeng, Silin; Zhang, Yaqing; Zou, Liangyu; Fu, Xuejun; Xu, Qianhui (Frontiers in Immunology, 2020)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune disorder mediated by NMDAR antibodies, typically manifesting as behavioral complaints, psychosis, seizures, movement disorders, hypoventilation, and autonomic dysfunction. In recent years, the predisposing factors and pathophysiological mechanisms of anti-NMDAR encephalitis have been tried to be clarified. It has been recognized that an overlap may be observed between anti-NMDAR encephalitis and inflammatory demyelinating disease. However, anti-NMDAR encephalitis is rarely associated with multiple sclerosis. Here, we describe a Chinese female patient diagnosed with relapsing remitting multiple sclerosis who developed anti-NMDAR encephalitis. Further, we discuss the previously reported literature.